Digitisation and the Future of Work - Melanie Arntz; Terry Gregory; Ulrich Zierahn (Wirtschaftsdienst)
Abstract Rapidly increasing computing power means that more and more activities that previously seemed reserved for humans can now be automated using machines and algorithms. This technological change has sparked a public debate about possible job losses and the threat of mass unemployment. From a scientific perspective, this is clearly exaggerated for four reasons: Firstly, the technological potential for automating jobs is often clearly overestimated. Secondly, by no means will every potential automation actually be put into operational practice. Thirdly, a division of labour between man and machine that adapts flexibly again and again often prevents job losses. And fourthly, automation releases compensation mechanisms that counteract the original displacement effect. An end to work is therefore not in sight, despite constantly increasing technical possibilities, even if this far reaching structural change presents new challenges for workers.